2006
DOI: 10.1159/000098655
|View full text |Cite
|
Sign up to set email alerts
|

Celecoxib and Curcumin Additively Inhibit the Growth of Colorectal Cancer in a Rat Model

Abstract: Background: Multiple studies have indicated that specific COX-2 inhibitors may prevent CRC. However, the long-term use of COX-2 inhibitors is not toxicity-free and may be limited due to its cardiovascular side effects. The present study was carried out to examine the chemopreventive effects of celecoxib and curcumin alone and in combination using the 1,2-dimethylhydrazine (DMH) rat model. Methods: Male rats were injected with DMH and randomly divided into four groups that consumed one of the following diets: (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 44 publications
0
35
0
1
Order By: Relevance
“…Tetrahydrocurcumin (THC) significantly decreases DMH-induced colon carcinogenesis [172] . Shpitz et al [173] showed that curcumin and celecoxib synergistically inhibit colorectal cancer progression in DMH-induced rat model. Several studies documented the inhibitory effects of curcumin on AOM-induced colon cancer [174] .…”
Section: Curcuminmentioning
confidence: 99%
“…Tetrahydrocurcumin (THC) significantly decreases DMH-induced colon carcinogenesis [172] . Shpitz et al [173] showed that curcumin and celecoxib synergistically inhibit colorectal cancer progression in DMH-induced rat model. Several studies documented the inhibitory effects of curcumin on AOM-induced colon cancer [174] .…”
Section: Curcuminmentioning
confidence: 99%
“…Several combinations of nonsteroidal anti-inflammatory drugs with other chemopreventive drugs have previously been investigated [Torrance et al 2000;Agarwal et al 1999]. Among these are celecoxib and curcumin, which in combination demonstrated a synergistic effect in inhibiting the growth of CRC cells in vitro and in vivo [Shpitz et al 2006;Lev-Ari et al 2005a, 2005b. Other studies have shown that curcumin and green tea synergistically inhibit cell proliferation and induce apoptosis in the ACF rat model and that a combination of celecoxib and difluoromethylornithine can reverse DNA hypomethylation on CRC in rats [Xu et al 2010;Pereira et al 2004].…”
Section: Discussionmentioning
confidence: 99%
“…Among the many mechanisms explaining its anticancer effects, curcumin was shown to interfere with the activity of the transcription factor NF-kB, suppress EGFR gene expression, and inhibit b-catenin-mediated transactivation and COX-2 expression [Anand et al 2008;Singh and Khar, 2006;Goel et al 2001]. Previous studies in our laboratory have demonstrated a synergistic effect between celecoxib (Celebrex, Pfizer, New York, USA), a COX-2 inhibitor, and curcumin, in the growth inhibition of CRC cells in vitro and in vivo [Shpitz et al 2006;Lev-Ari et al 2005a, 2005b, while others [Volate et al 2005] showed that curcumin alone had an effect in vivo, and decreased the number of ACF in rats after injection of AOM. The ability of curcumin to modulate ACF correlates with its ability to induce apoptosis.…”
Section: Introductionmentioning
confidence: 97%
“…Curcumin has also been shown to inhibit the mutagenic induction effect of UV rays. [42][43][44][45][46] Among various mechanisms, induction of apoptosis plays an important role in its anticarcinogenic effect. It induces apoptosis and inhibits cell-cycle progression, both of which are instrumental in preventing cancerous cell growth in rat aortic smooth muscle cells.…”
Section: Anti-cancer Effectmentioning
confidence: 99%
“…Curcumin induces apoptotic cell death by DNA-damage in human cancer cell lines, TK-10, MCF-7 and UACC-62 by acting as topoisomerase II poison. [48] In an animal study, rheumatoid arthritis induced by streptococcal cell wall, intraperitoneal injection of turmeric extract containing 4 mg total curcuminoids/kg/day for four days prior to www.wjpr.net phases. To test the efficacy of an oral preparation, a 30-fold higher dose of the curcuminoid preparation, given to rats four days prior to arthritis induction, reduced joint inflammation by 48%.…”
Section: Anti-cancer Effectmentioning
confidence: 99%